Hospital gastronomy helping to reduce malnutrition rates among hospitalized patients - Mariana Delega de Souza; Miyoko Nakasato (O Mundo da Saúde)
Different factors are involvedin undernourishment in hospitalized patients. Hospital diet is important because it guarantees the delivery of nutrients to compromised patient, preserving or recovering the nutritional state, and is being adapted to the tendencies of gastronomy. This work aimed at reasoning on hospital gastronomy as an ally in the recovery of the nutritional state of hospitalized undernourished patients. It has been realized by means of bibliographical revision that used scientific publications of the last 10 years. Foods do not induce people to want to feed themselves by their chemical composition; they also have to be attractive due to other components, such as flavor, appearance and the meanings that bring to the life of people, because eating is a social act. During a hospital stay the acceptance of feeding by patientsis influenced by psychological aspects, symptoms associated to the diseases, modifications of consistency in diet, restrictions of ingredients that cause monotony and even the waypeople are cared. In order to favor the acceptance to feed, it is important to work the organoleptic aspect of foods, in addition to giving the food tray for patients a good esthetic presentation, to consider feeding habits, to care with courtesy and to provide comfort to the act of feeding. Hospital gastronomy, which unites dietetic prescription and food restrictions for the elaboration of healthful, nutritious, attractive and flavorful food, helps tomake hospital diets, known by being flavorless, participate in therapeutics, adding pleasure to the nutritional value of foods. More field studies are required for verifying statistically how that benefit is necessary.